2017
DOI: 10.1111/1365-2664.13031
|View full text |Cite
|
Sign up to set email alerts
|

Species wood density and the location of planted seedlings drive early‐stage seedling survival during tropical forest restoration

Abstract: The success of restoration projects is known to vary widely, with outcomes relating to numerous biotic and abiotic factors. Though many studies have examined the factors associated with long‐term restoration success, few have examined which factors impact the establishment of restoration plantings. In Australia's Wet Tropics, we used a large replicated restoration experiment to assess seedling survival for 24 native rainforest species commonly used in local restoration efforts. The experiment allowed for a rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 64 publications
3
49
3
4
Order By: Relevance
“…Specifically, we show that species wood density is an important predictor for both seedling growth and survival (Charles et al 2018) and clearly demonstrates the mortalitygrowth tradeoff strategies commonly employed by tropical trees. Species selection can be difficult, because growth rates are affected by combinations of biotic and abiotic factors operating across multiple spatial scales.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Specifically, we show that species wood density is an important predictor for both seedling growth and survival (Charles et al 2018) and clearly demonstrates the mortalitygrowth tradeoff strategies commonly employed by tropical trees. Species selection can be difficult, because growth rates are affected by combinations of biotic and abiotic factors operating across multiple spatial scales.…”
Section: Resultsmentioning
confidence: 58%
“…This result was unexpected given the commonly observed negative relationship between seed mass and growth in both restoration plantings (Baraloto et al 2005, Mart ınez-Garza et al 2013a) and in mature forests (Osunkoya et al 1993, Poorter and Rose 2005, Poorter et al 2008). While larger seeded species commonly display higher survival rates (Baraloto et al 2005, Poorter et al 2008, with greater establishment success promoting further growth (Schupp 1995), our recent study of survival in the same experiment revealed a negative relationship between seed mass and seedling survival, though this was not significant (Charles et al 2018). This legacy effect may also be enhanced by the positive relationship between seed mass and specific root length (SRL; Westoby et al 1992), which can reduce post-planting seedling stress (Grossnickle 2005) and increase seedling growth (Wright and Westoby 1999).…”
Section: Effects Of Functional Traits On Seedling Growthmentioning
confidence: 93%
See 3 more Smart Citations